High Sensitivity Biosensor Designed by Graphene on Insulator MZI Waveguide - Irawan, Dedi (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2018)
We designed a high sensitivity optical biosensor based on Mach-zehnder Interferometer (MZI) by covering the silica waveguide with single atomic layer of graphene material. Graphene was applied to the arm of MZI in certain length. The upper arm was set an important key as the reference signal. The sensor sensitivity was determined mathematically from the power difference launched at the output ports. Our results shows novel optical absorption of hybrid waveguide applied in MZI arm. The presence of sample, which induces the effective index of the hybrid waveguide, significantly changes the phase of light propagation and the power ratio at the output ports which determines the sensitivity. Finally, we showed the effect of the distance between the graphene to the core and the length of graphene on waveguide of MZI.